Implementation of problem-based learning modules in an introduction to public health course - Matsuda, Yui; Falcon, Ashley; Porter, Andrew; Royer, Aaron; Mohnkern, Leah; Vergara, Diana; Valiente, Yesenia (Frontiers in Public Health, 2024)
Introduction With traditional lecture-based learning methods often criticized for their limited ability to foster critical thinking and cognitive engagement, problem-based learning (PBL) has emerged as a promising alternative. This research investigates the impact of PBL on student learning outcomes, specifically focusing on the development of higher-order thinking skills, communication, growth mindset, and metacognitive abilities. Methods PBL was implemented in an undergraduate public health course at a private university in the southeast US. The study was conducted in the Spring of 2022 using a convergent mixed-methods approach. Quantitative data were derived from university-wide Quality Enhancement Plan surveys and a course-specific PBL survey, which were analyzed using Repeated Measures ANOVA to assess changes in student perceptions over time. Additionally, qualitative data from open-ended survey questions were analyzed through thematic analysis, providing deeper insights into the students’ experiences and perceptions of PBL. Results Results indicated significant improvements in student communication skills, growth mindset, and metacognitive abilities across the semester. The thematic analysis of qualitative responses corroborated these findings, revealing enhanced team collaboration, active engagement in problem-solving, and increased comfort with complex real-world issues. Discussion The findings contribute to the growing body of evidence supporting PBL and offer practical insights for implementing PBL in public health education. The study also highlights the need for institutional support in adopting innovative teaching methods like PBL, emphasizing faculty development, resource allocation, and curriculum design.